Problem Solving in Nishikant Kamat’s Movie Drishyam - ., Yoeanita; Kurniadi, D (KnE Social Sciences, 2018)
This research is related to the process of problem solving that happened in the Nishikant Kamat movie’s Drishyam. The purpose of this research is to find what kinds of problem solving done in this movie and how those kinds implemented in the movie. The theory used in this research was the problem-solving theory proposed by Redoni (2017) because this theory divides the kinds of problem solving into four categories they are: comprehend the problem, arrange the plan, run the plan, and test and retest the plan that was studied by using Khotari (1990) qualitative method. The result of this research was the actor could comprehend the problems that make them have good strategies to arrange some plans and run it. After that, the actor tests and re-tests all his plans to make the problem solved well. This research is important for people getting into problem as they will find easy to solve problems by knowing the kinds of problem solving. Keywords: Problem Solving, Problem Comprehension, Arrangement Problem, Test and Re-test Planning